Quranic scientific miracles in Metals A Comparative study with the Bible - Al-Dulaimi, Muhammad Abed Ali Dhahi (International Journal of Psychosocial Rehabilitation, 2020)
This paper is entitled: Quranic scientific miracles in Metals: A Comparative study with the Bible. The study included minerals: gold, silver and iron in terms of their presence in the texts of the Koran and the Torah with a study of all the miraculous aspects concerning these minerals and compared with their counterparts in the Old Testament. The results of this study showed the high accuracy of the use of these minerals in the Holy Quran with the compatibility of scientific aspects with the findings of modern science and the absence of these concepts of what is found in these minerals in the Old Testament. This indicates that there is no doubt that the Koran is the word of God Almighty revealed to the Prophet Muhammad.